Evaluation of Death Patients on the Deceased Kidney Waiting List of Bursa Uludağ University Medical Faculty According to Years by Gender, Age, Blood Type, Dialysis Type - Mehmet Fethullah Aydın; Abdülmecit Yıldız; Ayşegül Oruç; Mehmet Sezen; Kadir Günseren; Mehmet Çiçek; Sahriye Keskin; İbrahim Ethem Arslan; Rafet Oflaz; Kerem Selimoğlu; İlknur Arslan; Alparslan Ersoy; et al. (Turkish Journal of Internal Medicine, 2021)
Evaluation of Death Patients on the Cadaveric Kidney Waiting List of Bursa Uludağ University Medical Faculty According to Years by Gender, Age, Blood Type, Dialysis Type In Turkey, there is 22953 end-stage kidney disease patient in national deceased kidney waiting list (1). According to the 2019 Registry Report of the Turkish Society of Nephrology, the number of patients receiving dialysis is 64633. The number of patients receiving hemodialysis (HD) and peritoneal dialysis (PD) are 61341 and 3292, respectively (2). However, patients registered on the national kidney waiting list consist of preemptive, PD, and HD patients. Due to the increase in the average life expectancy of the elderly population in our country, chronic kidney disease and comorbid diseases are increasing day by day. In this study, the characteristics of the patients who died on the deceased kidney waiting list of our kidney transplant center were evaluated retrospectively. Our center's patient data were obtained from Transplantation Dialysis Monitoring System records. Turkey’s general patient data were obtained from the Turkish Statistical Institute and the 2019 Registry Report of Turkish Society of Nephrology. In our center, the number of patients who died on the kidney waiting list from deceased donors was 350 (HD: 273, PD: 73, preemptive: 4). The number of female patients was 134 (38.2%) and the number of male patients was 216 (61.4%). The age distribution of the patients 0-9: 5%, 1.4, 10-19: 5 1.4%, 20-29: 14 4%, 30-39: 36 10.2%, 40-49: 62 17%, 7, 50-59: 100 28.5%, 60-69: 96 27.4%, 70-79: 31 8.8%, and 80-89: 1 0.2%. The distribution of blood groups of patients was consistent with the data in Turkey. [A Rh (+): 41.4%, A Rh (-): 3.7%, 0 Rh (+): 29.1%, 0 Rh (-): 6%, B Rh (+): 10.6%, B Rh (-): 0.6%, AB Rh (+): 7.1% and AB Rh (-): 1.4%]. The distribution of our patients by gender and kidney replacement therapies was in line with the 2019 Registry Report of Turkish Society of Nephrology. The number of patients who died by years is shown in figure 1. In our study, deaths between the age range of 50-59 and 60-69 registered in our center and died constitute 56% of the total deaths. Patients with chronic kidney failure have a high risk of death between the ages of 50 and 69. In one study, the course of Covid-19 disease caused by the SARS-CoV-2 virus is terrifying in elderly, co-morbid diseases, and male patients (3). Also, COVID-19 is severe and fatal in chronic kidney disease. With the COVID-19 disease being a pandemic in the world in 2020, according to the data of the current World Health Organization (WHO) dated 07.02.2021, 105,394,301 cases were detected in the world 2,302,302 deaths occurred (4). When we look at the distribution of cases by years, the death rate in 2020 is the highest. Although this suggests that this situation is related to the COVID-19 disease, the relationship with COVID-19 could not be determined since the causes of the deaths of these cases could not be reached from the death notification system of Ministry of Health. Due to the high mortality rates in the range of 50 to 69 years of age of patients in kidney transplant waiting lists, especially for patients with advanced age with chronic kidney disease "Turkey Kidney Diseases Prevention and Control Program" (5) to be controlled although work on the policy for new infectious diseases needs to be improved.